Analisis Verbal Abuse Pada Tingkat Emosional Remaja Awal di SMP N I Huristak - Nurmina Wati Hasibuan; Dika Sahputra (Indonesian Counselor Association (IKI), 2024)
This research aims to analyze verbal abuse or verbal violence at the emotional level of early adolescents at SMP N I Huristak. The specific impact analyzed from this research is the emotional level of teenagers who experience humiliation, ridicule and criticism. This type of qualitative research uses a descriptive approach, namely presenting data and information by describing it as it really is. The subjects in this research were 6 (six) students of SMP N I Huristak who experienced verbal violence. The data collection technique uses domain analysis which is carried out starting from data reduction, data presentation, and drawing conclusions. The results of the research showed that 6 (six) subjects had different emotional conditions, this was seen from the aspects of behavior, emotions and social relationships, namely four subjects had bad emotional behavior which resulted in stress disorders, decreased self-confidence and difficulty interacting. with colleagues, while two subjects had good emotional behavior because they had support from people around them such as friends and parents so that verbal abuse did not have a negative impact on their personality. It is hoped that this research will become a recommendation for policy makers to continue to instill character education for teenage students and provide counselors in each school to ensure that students' mental health is maintained.